Habits in the Kitchen: On the Application of Recipes for the Good Life - Valgenti, Robert T. (Aisthesis, 2024)
What does it mean to apply a recipe? In this essay I examine how habit and improvisation contribute to the application of recipes. Application entails more than following technical instructions; it involves strategies for critically reading, understanding, and performing recipes in a manner that contributes to their transmission and transformation. Application draws upon our habits and prior knowledge to respond to the contingencies of new situations and highlights future possibilities that require adaptation and transformation. I thus argue that one should view recipes as ethical texts, which in this context of application means that they are something more than rigid technical guides for cooking, and more than mere recordings of cultural and historical knowledge to be reproduced: as an essential element of human gastronomy, the application of a recipe involves habit and improvisation working together in the pursuit of the good life.